Boats on the rocks: Late prehistoric nautical iconography and landscape, from Northwest Iberia to Scandinavia - Marta Díaz-Guardamino; Boel Bengtsson; Ellie Newton; Ana M. S. Bettencourt; Johan Ling; Juan Latorre-Ruiz; Hugo A. Sampaio; Diogo Marinho (PLoS ONE, 2026)
This paper offers a comparative analysis of prehistoric rock art boat depictions found across northwest Iberia and southern Scandinavia. We apply advanced digital documentation techniques, including high-resolution 3D recording and Geographic Information Systems (GIS)-based landscape analysis, to study the Iberian petroglyphs’ iconography and geographic placement in detail. The study identifies significant typological and iconographic parallels between Northwest Iberia and Nordic images, which provides a comparative basis to propose a Late Bronze Age chronology (c. 1300–800 BCE) for the Iberian examples. This shared iconography supports existing hypotheses concerning extensive long-distance connectivity and maritime trade networks across Atlantic Europe, particularly regarding the movement of metals like copper and tin. Furthermore, the GIS analysis confirms that nearly all Iberian sites, whether coastal or far inland, maintain a crucial visual or physical relationship with navigable waters, such as the ocean or major river systems. Ultimately, the authors propose that this rock art reflects both advancements in boat technology and the ritual and cosmological beliefs of maritime communities engaged in transregional exchange.